Desain Bahan Ajar dan Sumber Belajar Berbasis Pengalaman Belajar dan Outcome di Tingkat Sekolah/Madrasah dan Perguruan Tinggi - Nasution, Ummi Nadrah; Qomariah, Siti; Utari, Anggie Sri; Halimah, Siti (MUDABBIR Journal Research and Education Studies, 2024)
This study aims to design an outcomes-based learning experience in Islamic Religious Education (PAI) that focuses on spiritual development and the application of religious values ??in real life. This approach is expected to go beyond mere academic achievement by emphasizing behavioral transformation and internalization of students' religious values. The research method used is a qualitative study with a library research approach. Data were collected through document analysis in the form of books, journals, and scientific articles. The results of the study indicate that outcomes-based learning designed with a contextual approach and based on real experiences can improve students' religious understanding, spiritual appreciation, and skills in applying religious teachings in everyday life. Thus, PAI learning not only functions as a transfer of knowledge, but also as a means of character and spirituality formation that is relevant to the challenges of modern life.